Análisis del modelo pedagógico en inicial uno del Centro Infantil Primero de Mayo. - Solis Gamboa, Evelyn Carolina (2018)
The purpose of this work is to analyze the pedagogical model that assumes and develops the Primero de Mayo Children's Center in Initial Education, sub-level I. For this purpose, a bibliographic review was made on the history and evolution of the pedagogical models of initial education. In the educational model, the Froebeliano, Agazziano, Montessoriano and Decroliano curricula that for a long time were valid in pre-school education are explained, since they proposed innovative strategies, focusing on the child's conception and the importance of early childhood care. Over time and with the various changes that have been presented around education, new proposals in relation to institutional pedagogical models as is the case of the socio-constructivist model. There was also a brief tour about the changes that the Initial Education Curriculum has had in recent years to reach a quality education. The second part analyzes the pedagogical model assumed by the institution and the inconsistencies that exist between the assumed model and what is developed in the teaching practice. In order to obtain information, observations were made, the director and teacher were interviewed and the Institutional Educational Project was analyzed. The third part outlines some conclusions and recommendations. To carry out this analysis, the qualitative method was used through observation, field diaries, interviews and surveys until the pedagogical model used at this level was identified.